2011
DOI: 10.1097/mbp.0b013e328344c6db
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of morning and evening dosing of amlodipine/valsartan combination in hypertensive patients uncontrolled by 5 mg of amlodipine

Abstract: These results indicate that, in patients with BP uncontrolled by amlodipine (5 mg), morning and evening treatment with amlodipine/valsartan combination have similar effects on circadian BP, especially when 24-h mean values are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 20 publications
0
13
1
9
Order By: Relevance
“…Among the patients using ABPM in this study, those with the 8‐week OA FDC showed greater SBP‐lowering effects than those receiving DA. Furthermore, the ABPM SBP reduction in our patients receiving the OA (20 mg/5 mg) FDC was greater than for the patients in another study receiving valsartan/amlodipine FDC (160 mg/5 mg) for 8 weeks where their BPs were uncontrolled by amlodipine (5 mg) [16].…”
Section: Discussioncontrasting
confidence: 62%
“…Among the patients using ABPM in this study, those with the 8‐week OA FDC showed greater SBP‐lowering effects than those receiving DA. Furthermore, the ABPM SBP reduction in our patients receiving the OA (20 mg/5 mg) FDC was greater than for the patients in another study receiving valsartan/amlodipine FDC (160 mg/5 mg) for 8 weeks where their BPs were uncontrolled by amlodipine (5 mg) [16].…”
Section: Discussioncontrasting
confidence: 62%
“…A recent meta-analysis has shown that in hypertensive patients, every 10 mmHg increase in night-time BP is associated with a 15% higher cardiovascular risk also after controlling for daytime BP [15]. In the setting of OSA, night-time BP surges, a nondipping BP profile and increased BP variability are characteristic [16][17][18], though data have not been consistent [19]. Accordingly, in the Heart Outcomes Prevention Evaluation study, evening dosing of ramipril was associated with a decreased cardiovascular risk, despite the only mild decreases in clinic BP, a fact that was attributed to better night-time BP control [20].…”
Section: Discussionmentioning
confidence: 95%
“…We thus conducted the statistical analysis to test for noninferiority against a one‐sided alternative hypothesis at the 2.5% significance level and a power of 80%. By assuming a standard deviation for the changes in nocturnal BP of 7.0 mm Hg and a clinically significant difference in the nocturnal brachial SBP reduction between the morning and bedtime administrations from the baseline of 0.43 mm Hg (based on a previous report), the sample size would be 23 patients. Adjusting by 10% for loss to follow‐up or dropout of patients, a final total of 26 patients were needed at randomization.…”
Section: Methodsmentioning
confidence: 99%